Metal contamination and radiological risk assessment in the coastal zone of Wadi Ghadir outlet, Red Sea, Egypt - Saleh, Gehad M.; Semary, Hatem E.; Lasheen, El Saeed R.; Kamar, Mohamed S.; Elkelish, Amr; Sami, Mabrouk; Sanislav, Ioan V.; Abdelaal, Ahmed (Frontiers in Environmental Science, 2025)
This study evaluated concentrations, spatial distribution, and ecological–health risks of nine heavy metals in 25 surface sediment samples from Wadi Ghadir outlet, southeastern Red Sea coast, Egypt. The sediments were sandy (>94%), alkaline (pH 8.12), and contained moderate organic matter (5.6%–8.9%). Metal concentrations (mg/kg) followed: Fe > Ba > Cr > Zn > Ni > V > Pb > Cu > Co. Ba, Cr, and Ni exceeded Canadian soil quality guidelines and global Earth crust backgrounds, while others remained below. Spatially, Ba, Ni, and V peaked in the north, Co, Cr, and Zn in central sites, and Pb, Cu, and Fe in the south. Multivariate analyses indicated both natural and anthropogenic sources. Enrichment and contamination factors showed moderate enrichment for Pb and Ni, and considerable contamination for Ni. Geo-accumulation index (Igeo >5) and pollution load index (PLI; 1.62) confirmed significant contamination. Ecological risk indices (PERI <150, Eri <40) suggested overall low risk, with Ni and Pb most concerned. Additional sediment quality indices (MERMQ, TRI, mHQ) pointed to medium–moderate ecological and toxic risks, while human health evaluation revealed low non-carcinogenic and carcinogenic risks. Radiological analyses of 232Th, 40K, and 226Ra revealed concentrations (Bq/Kg) and dose indices within global safety limits, indicating negligible radiological risk.